STUDI KETEBALAN KULIT DAN LETAK BAGIAN IMPLAN PADAPERTUNASAN DAN PERTUMBUHAN AWAL TIGA JENIS TANAMAN UWI ( Dioscorea alata L.) - ,, Wuryantoro (JURNAL AGRI-TEK, 2018)
The “uwi” plant (Dioscorea sp.) as one of the most potent types of potatoes supports the food diversity and food security in the future. This plant is easy to cultivate and tolerant to critical upland. The objective of this research is to obtain the most efficient and effective method of planting of uwi plants to overcome the limitations of commercial seedlings. The research was conducted in Agronomy Laboratory of Agriculture Faculty of Universitas Merdeka Madiun from September to November 2017, using a randomized block design consisting of 3 factors repeated three times. These factors are the implant tuber part, thick implant, and type uwi D. alata. Three types of media are used as blocks consisting of soil media, sand and husk. Observations included the growth rate of sprout, shoot length, bud stem diameter, number of leaves and dry weight of buds. The results showed that to overcome the limitations of uwi seedlings can use all parts of the tuber without distinguishing the type. The part of tuber implants for seedlings only causes the growth of buds to be rather slow, and possibly only impacts on delayed planting and harvesting. While the skin of tuber peel can still be used for seedlings, although shoots that grow smaller, which can be overcome with a more optimal cultivation techniques. Keywords : implant part, tuber thick skin, “uwi” types, germination